Angiotensin II Receptor 1 Blockage Limits Brain Damage and Improves Functional Outcome After Brain Injury in Aged Animals Despite Age-Dependent Reduction in AT1 Expression - Timaru-Kast, Ralph; Gotthardt, Philipp; Luh, Clara; Huang, Changsheng; Hummel, Regina; Schäfer, Michael K. E.; Thal, Serge C. (Frontiers in Aging Neuroscience, 2019)
Traumatic brain injury (TBI) is a frequent pathology and associated with poor outcome in the aged population. We recently observed accelerated cerebral inflammation in aged mice in response to TBI. Candesartan is a potent specific inhibitor of angiotensin II receptor type 1 (AT1) which limits cerebral inflammation and brain damage in juvenile animals after experimental TBI. In the present study, we show significantly lower posttraumatic AT1 mRNA levels in aged (21 months) compared to young (2 months) mice. Despite low cerebral At1 expression, pharmacologic blockade by treatment with candesartan (daily, beginning 30 minutes after experimental TBI by controlled cortical impact [CCI]) was highly effective in both young and aged animals and reduced histological brain damage by -20 % after five days. In young mice neurological improvement was enhanced by AT1 inhibition five days after CCI. In old animals, candesartan treatment reduced functional impairment already on day 3 after TBI and post-traumatic body weight loss was attenuated. Candesartan reduced microglial activation (-40 %) in young and aged animals, and neutrophil infiltration (-40 - 50 %) in aged mice, whereas T-cell infiltration was not changed in both age groups. In young animals, markers of anti-inflammatory microglia M2a polarization (arginase 1 [Arg1], chitinase3-like 3 [Ym1]) were increased by candesartan at days 1 and 5 after insult. In aged mice five days after insult expression of Arg1 was significantly higher independent of the treatment, whereas Ym1 gene expression was further enhanced by AT1 inhibition. Despite age dependent posttraumatic differences in At1 expression levels, inhibition of AT1 was highly effective in a posttreatment paradigm. Targeting inflammation with candesartan is therefore a promising therapeutic strategy to limit secondary brain damage independent of the age.